2011
DOI: 10.1128/aem.02788-10
|View full text |Cite
|
Sign up to set email alerts
|

Selection Pressure Required for Long-Term Persistence of bla CMY-2 -Positive IncA/C Plasmids

Abstract: Multidrug resistance bla CMY-2 plasmids that confer resistance to expanded-spectrum cephalosporins have been found in multiple bacterial species collected from different hosts worldwide. The widespread distribution of bla CMY-2 plasmids may be driven by antibiotic use that selects for the dissemination and persistence of these plasmids. Alternatively, these plasmids may persist and spread in bacterial populations in the absence of selection pressure if a balance exists among conjugative transfer, segregation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 53 publications
4
94
1
Order By: Relevance
“…There was no plasmid loss by the bacteria (23,32). The plasmid-bearing bacteria experienced a fitness cost represented by a fractional reduction of 0.05 (23,33) in the maximum growth rate, r. Plasmid transfer was a frequency-dependent transmission process; the number of plasmid-free E. coli bacteria acquiring the gene through plasmid conjugation was ␤(N plϩ ϫ N plϪ /N tot ) (23). The value of ␤ was 0.004/hour and corresponded to the dynamics of transfer of the exemplar bla CMY-2 (23).…”
Section: Lytic Cycle After Prophage Inductionmentioning
confidence: 99%
“…There was no plasmid loss by the bacteria (23,32). The plasmid-bearing bacteria experienced a fitness cost represented by a fractional reduction of 0.05 (23,33) in the maximum growth rate, r. Plasmid transfer was a frequency-dependent transmission process; the number of plasmid-free E. coli bacteria acquiring the gene through plasmid conjugation was ␤(N plϩ ϫ N plϪ /N tot ) (23). The value of ␤ was 0.004/hour and corresponded to the dynamics of transfer of the exemplar bla CMY-2 (23).…”
Section: Lytic Cycle After Prophage Inductionmentioning
confidence: 99%
“…When the benefits of carriage outweigh the costs, plasmids can be maintained by positive selection [4], although over longer time-scales, beneficial accessory genes may be selected to relocate to the chromosome [5]. When the costs outweigh the benefits, plasmids should be lost to purifying selection [6], unless this is counteracted by sufficiently high rates of conjugative transfer or sufficiently rapid compensatory evolution to ameliorate the cost of carriage [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that carriage of bla CMY-2 IncA/C plasmids imposes a fitness cost on the host bacteria, leading to the conclusion that long-term maintenance of IncA/C plasmids requires selective pressure (25). A mathematical model of ESC r E. coli populations in cattle suggests that E. coli strains harboring bla CMY-2 IncA/C plasmids could persist during periods of low selective pressure even if they grow slower than other com-mensal E. coli strains if frequent horizontal transfer of bla CMY-2 IncA/C plasmids occurs or a sufficient fraction of E. coli bacteria ingested by cattle contain bla CMY-2 IncA/C plasmids (26).…”
mentioning
confidence: 99%